Spatiotemporal Distribution of Two Euschistus spp. Stink Bugs (Hemiptera: Pentatomidae) in Southeastern Farmscapes. Issue 1 (23rd January 2022) - Grabarczyk, Erin E; Mizell, Russell F; Greene, Jeremy K; Herzog, Gary A; Tillman, P Glynn; Cottrell, Ted E
Abstract: Stink bugs (Hemiptera: Pentatomidae) are ubiquitous, cryptic, phytophagous pests that are found in many crops. In agroecosystems, individuals disperse from adjacent noncrop hosts and tend to aggregate or cluster within fields. In this study, we characterized the distribution of Euschistus servus (Say) and Euschistus tristigmus (Say) (Hemiptera: Pentatomidae) over 2 yr at three southeastern United States farmscapes. Stink bugs were captured in pheromone-baited traps, and Spatial Analysis by Distance Indices (SADIE) used to identify the location of significant aggregations by habitat type and season. Euschistus servus adults were more likely to be captured in pecan orchards, cotton, other crops, or unmanaged habitats than in woodland habitats. Significant aggregations of E. servus were detected in a variety of habitats including pecan, corn, cotton, peanut, and tobacco, as well as fallow and hay fields, pastures, and hedgerows. Fewer adult E. tristigmus were captured than E. servus adults, and E. tristigmus adults were typically trapped and aggregated in woodland habitats. The resulting data provide an important understanding regarding the seasonal movement and relative abundance levels of stink bug populations, which are critical to the development of integrated pest management strategies.